2015
DOI: 10.1016/j.biopsych.2014.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Global Cortical Thinning in Acute Anorexia Nervosa Normalizes Following Long-Term Weight Restoration

Abstract: Structural brain anomalies in AN as expressed in CT and subcortical volume are primarily the consequence of malnutrition and unlikely to reflect premorbid trait markers or permanent scars, but longitudinal data are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

16
143
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(163 citation statements)
references
References 87 publications
16
143
4
Order By: Relevance
“…The ongoing debate on state or trait characteristics of brain structure abnormalities in patients with AN was renewed by two recent studies. King et al [22] demonstrated in an acute phase of AN significantly reduced cortical thickness in large parts of the cerebral cortex, whereas in recovered patients with long-term weight restoration these cortical thickness differences were not found, indicating that cortical thickness reductions in AN might be dependent on the current symptomatic and might therefore reflect a state marker of the disease. In accordance with this study, our group recently showed that cortical thickness reduction in acute AN correlated with symptom severity of the disease.…”
Section: Introductionmentioning
confidence: 93%
“…The ongoing debate on state or trait characteristics of brain structure abnormalities in patients with AN was renewed by two recent studies. King et al [22] demonstrated in an acute phase of AN significantly reduced cortical thickness in large parts of the cerebral cortex, whereas in recovered patients with long-term weight restoration these cortical thickness differences were not found, indicating that cortical thickness reductions in AN might be dependent on the current symptomatic and might therefore reflect a state marker of the disease. In accordance with this study, our group recently showed that cortical thickness reduction in acute AN correlated with symptom severity of the disease.…”
Section: Introductionmentioning
confidence: 93%
“…Past studies often found widespread reduced gray matter and white matter volumes in anorexia nervosa (Van den Eynde et al, 2012). Such reduced brain volumes or cortical thickness typically recover with illness remission though, suggesting staterelated factors (King et al, 2015). Importantly, findings during the acute state could be effects of acute dehydration, starvation or excessive exercise (Streitburger et al, 2012), and controlling for those factors may help to identify brain structures that drive illness behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Anorexia nervosa (AN) is a serious disorder that is characterized not only by psychological, social and somatic factors (according to ICD-10 and DSM-IV-TR) but also by metabolic changes within the central nervous system [1,2], by structural alterations in brain volume and cortical thickness [3], and functional alterations targeting network connectivity [4]. The latter changes seem to be associated with core symptoms of AN and impaired performance in executive functions (EF) comprising flexibility, inhibition, visuospatial processing and working memory (WM) [4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%